(7x-8) mũ 2=36
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, (x-35)-120=0
x-35=120+0
x-35=120
x=120+35
x=155
b,7x-8=713
7x=713+8
7x=721
x=721:7
x=103
c,4x:17=0
4x=0.17
4x=0
x=0:4
x=0
d,75+(131-x)=205
131-x=205-75
131-x=130
x=131-130
x=1
e,2x-36=4^6:4^3
2x-36=4^6-3
2x-36=4^3
2x-36=48
2x=48-36
2x=12
x=12:2
x=6
f, 2011^2.2011^x=2011^6
2011^x=2011^6: 2011^2
2011^x=2011^6-2
2011^x=2011^4
x=4
bn
\(\text{a/ ( x-35 ) - 120 = 0}\)
\(\Rightarrow\left(x-35\right)=120\)
\(\Rightarrow x=120+35\)
\(x=155\)
\(\text{b/ 7x - 8 = 713}\)
\(\Rightarrow7x=713+8=721\)
\(x=721:7=103\)
\(\text{c/ 4x : 17 = 0}\)
\(4x=0\)
\(x=0\)
\(\text{d/ 75+(131-x) = 205}\)
\(131-x=205-75=130\)
\(x=131-130=1\)
\(e.2x-36=4^6:4^3\)
\(2x-36=4^3=64\)
\(2x=64+36=100\)
\(x=100:2=50\)
\(f.2011^2.2011^x=2011^6\)
\(\text{Ta có công thức }:x^n.x^m=x^{n+m}\)
\(\Rightarrow x=6-2=4\)
`Answer:`
a, `4x^2-24x+36=(x-3)^3`
`<=>4(x^2-6x+9)-(x-3)^3=0`
`<=>4(x-3)^2-(x-3)^3=0`
`<=>(x-3)^2.(4-x+3)=0`
`<=>(x-3)^2.(7-x)=0`
`<=>x-3=0` hoặc `7-x=0`
`<=>x=3` hoặc `x=7`
b, `(8x^3-7x^2):x^2=3x+\sqrt{\frac{9}{25}}`
`<=>8x^3:x^2-7x^2:x^2=3x+\sqrt{\frac{9}{25}}`
`<=>8x-7=3x+\sqrt{\frac{9}{25}}`
`<=>8x-7=3x+3/5`
`<=>8x=3x+\frac{38}{5}`
`<=>8x-3x=3x+\frac{38}{5}-3x`
`<=>5x=\frac{38}{5}`
`<=>x=\frac{38}{25}`
1. \(A+7x^2y-5xy^2-xy=x^2y+8xy^2-5xy\)
\(\Rightarrow A+7x^2y-x^2y-5xy^2-8xy^2-xy+5xy=0\)
\(\Rightarrow A+6x^2y-13xy^2+4xy=0\)
\(\Rightarrow A=-6x^2y+13xy^2-4xy\)
2. \(4xy^2-7x+1-A=3x^2-7x-1\)
\(\Rightarrow4xy^2-3x^2-7x+7x+1+1-A=0\)
\(\Rightarrow4xy^2-3x^2+2-A=0\)
\(\Rightarrow A=4xy^2-3x^2+2\)
\(a.3x^2-12xy=3x\left(x-4y\right)\)
\(b.x^2+7x-2\left(x+7\right)=x\left(x+7\right)-2\left(x+7\right)=\left(x-2\right)\left(x+7\right)\)
\(c.8x^3-8x^2+2x=2x\left(4x^2-4+1\right)=2x\left(2x-1\right)^2\)
\(d.x^2-y^2+12y-36=x^2-\left(y-6\right)^2=\left(x-y-6\right)\left(x-y+6\right)\)
Bài làm
a) 3x2 - 12xy
= 3x( x - 4y )
b) x2 + 7x - 2( x + 7 )
= x( x + 7 ) - 2( x + 7 )
= ( x + 7 )( x - 2 )
c) 8x3 - 8x2 + 2x
= 2x( 4x2 - 4x + 1 )
= 2x( 2x - 1 )2
d) x2 - y2 + 12y - 36
= x2 - ( y2 - 12y + 36 )
= x2 - ( y2 - 2.y.6 + 62 )
= x2 - ( y - 6 )2
= ( x - y + 6 )( x + y - 6 )
# Học tốt #
1. 2x=16\(\Rightarrow\)X=4
2. 22x-1=27
\(\Rightarrow\)27=22.4-1
Vậy x =4
1: Ta có: \(\left(7x-3^2\right):5=8\)
\(\Leftrightarrow7x-9=40\)
hay x=7
1: x^2-9x+8=0
=>(x-1)(x-8)=0
=>x=1 hoặc x=8
2: 3x^2-7x+4=0
=>3x^2-3x-4x+4=0
=>(x-1)(3x-4)=0
=>x=4/3 hoặc x=1
3: 2x^2+5x-7=0
=>(2x+7)(x-1)=0
=>x=1 hoặc x=-7/2
4: 3x^2-9x+6=0
=>x^2-3x+2=0
=>x=1 hoặc x=2
5: x^2+2x-3=0
=>(x+3)(x-1)=0
=>x=-3 hoặc x=1
`@` `\text {Answer}`
`\downarrow`
`1)`
\(x^2 - 9x + 8?\)
\(x^2-9x+8=0\)
`<=>`\(x^2-8x-x+8=0\)
`<=> (x^2 - 8x) - (x - 8) = 0`
`<=> x(x - 8) - (x-8) = 0`
`<=> (x-1)(x-8) = 0`
`<=>`\(\left[{}\begin{matrix}x-1=0\\x-8=0\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=1\\x=8\end{matrix}\right.\)
Vậy, nghiệm của đa thức là `S = {1; 8}`
`2)`
\(3x^2 - 7x + 4 =0\)
`<=> 3x^2 - 3x - 4x + 4 = 0`
`<=> (3x^2 - 3x) - (4x - 4) = 0`
`<=> 3x(x - 1) - 4(x - 1) = 0`
`<=> (3x - 4)(x-1) = 0`
`<=>`\(\left[{}\begin{matrix}3x-4=0\\x-1=0\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}3x=4\\x=1\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=\dfrac{4}{3}\\x=1\end{matrix}\right.\)
Vậy, nghiệm của đa thức là `S = {4/3; 1}`
`3)`
\(2x^2 + 5x - 7=0\)
`<=> 2x^2 - 2x + 7x - 7 = 0`
`<=> (2x^2 - 2x) + (7x - 7) = 0`
`<=> 2x(x - 1) + 7(x - 1) = 0`
`<=> (2x+7)(x-1) = 0`
`<=>`\(\left[{}\begin{matrix}2x+7=0\\x-1=0\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}2x=-7\\x=1\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=-\dfrac{7}{2}\\x=1\end{matrix}\right.\)
Vậy, nghiệm của đa thức là `S = {-7/2; 1}.`
\(\left(7x-8\right)^2=36\)
\(\left(7x-8\right)^2=6^2=\left(-6\right)^2\)
\(\Rightarrow7x-8=6\text{ hoặc }7x-8=-6\)
\(7x=14\) \(7x=2\)
\(x=2\) \(x=\frac{2}{7}\)